Mating strategy predicts gene presence/absence patterns in a genus of simultaneously hermaphroditic flatworms. (1st December 2022) - Wiberg, R. Axel W.; Viktorin, Gudrun; Schärer, Lukas
Abstract: Gene repertoire turnover is a characteristic of genome evolution. However, we lack well‐replicated analyses of presence/absence patterns associated with different selection contexts. Here, we study ∼100 transcriptome assemblies across Macrostomum, a genus of simultaneously hermaphroditic flatworms exhibiting multiple convergent shifts in mating strategy and associated reproductive morphologies. Many species mate reciprocally, with partners donating and receiving sperm at the same time. Other species convergently evolved to mate by hypodermic injection of sperm into the partner. We find that for orthologous transcripts annotated as expressed in the body region containing the testes, sequences from hypodermically inseminating species diverge more rapidly from the model species, Macrostomum lignano, and have a lower probability of being observed in other species. For other annotation categories, simpler models with a constant rate of similarity decay with increasing genetic distance from M. lignano match the observed patterns well. Thus, faster rates of sequence evolution for hypodermically inseminating species in testis‐region genes result in higher rates of homology detection failure, yielding a signal of rapid evolution in sequence presence/absence patterns. Our results highlight the utility of considering appropriate null models for unobserved genes, as well as associating patterns of gene presence/absence with replicated evolutionary events in a phylogenetic context.